2013
DOI: 10.47893/ijmie.2013.1103
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Speed Parameters in Burnishing of Samples Fabricated by Fused Deposition Modeling

Abstract: Fused Deposition Modeling (FDM) is one of the best Rapid Prototyping Processes proved to be. Many researchers have produced a lot of work using the FDM process and many papers were published. Many researchers have concentrated on optimizing the parameters to obtain higher surface finish. Burnishing is one of the processes used to get higher surface finish on light metals. The present paper deals with the application of burnishing process on the samples fabricated with FDM. The burnishing process is applied on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ball burnishing process has been used by Vinitha et al (2012) to press the peaks of surface profile and fill in the valleys. The work piece was held between head and tail stock while burnishing tool in tool post of the lathe machine.…”
Section: Post-processing Techniquesmentioning
confidence: 99%
“…Ball burnishing process has been used by Vinitha et al (2012) to press the peaks of surface profile and fill in the valleys. The work piece was held between head and tail stock while burnishing tool in tool post of the lathe machine.…”
Section: Post-processing Techniquesmentioning
confidence: 99%
“…Hlinka 25 studied the impact of the laser surface treatment on DC01 steel and SAC305 lead-free solder paste. Vinitha et al 26 minimized the surface roughness of FDM parts using barrel burnishing. Ravoori et al 27 used a novel technique for providing additional heating to previously deposited layers in polymer additive manufacturing to improve the mechanical properties of PLA parts.…”
Section: Introductionmentioning
confidence: 99%
“…Ball honing is a cold working process by which the peaks of the surface roughness profile are compressed by a harder spherical tool. It has been observed that increasing the penetration depth and spindle speed improved the surface finish and increased hardness (Vinitha and Rao, 2012).…”
Section: Introductionmentioning
confidence: 99%